2016
DOI: 10.1200/jco.2016.68.3482
|View full text |Cite
|
Sign up to set email alerts
|

Statins Are Associated With Reduced Mortality in Multiple Myeloma

Abstract: The 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins) have activity in one of the pathways influenced by nitrogen-containing bisphosphonates, which are associated with improved survival in multiple myeloma (MM). To understand the benefit of statins in MM, we evaluated the association between statin use and mortality in a large cohort of patients with MM. Patients and MethodsFrom the Veterans Administration Central Cancer Registry, we identified patients diagnosed with MM between 1999 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 36 publications
2
61
1
Order By: Relevance
“…Thus, the mevalonate pathway promotes tumorigenesis by two mechanisms: (1) by enhancing protein prenylation, which is required for the activation of proteins involved in proliferation and migration, such as Ras and Rho; and (2) by stabilizing conformational mutant p53. It should be noted that the efficacy of statins (cholesterol lowering drugs) that inhibit the mevalonate pathway on tumor suppression is promising, yet they still remain controversial [68,69,70,71,72]. Our study may suggest the importance of knowledge of the p53 status in tumors treated with statins to determine their efficacy.…”
Section: Summary and Future Perspectivesmentioning
confidence: 78%
“…Thus, the mevalonate pathway promotes tumorigenesis by two mechanisms: (1) by enhancing protein prenylation, which is required for the activation of proteins involved in proliferation and migration, such as Ras and Rho; and (2) by stabilizing conformational mutant p53. It should be noted that the efficacy of statins (cholesterol lowering drugs) that inhibit the mevalonate pathway on tumor suppression is promising, yet they still remain controversial [68,69,70,71,72]. Our study may suggest the importance of knowledge of the p53 status in tumors treated with statins to determine their efficacy.…”
Section: Summary and Future Perspectivesmentioning
confidence: 78%
“…Patients receiving statins for at least 5 years have been found to have a 47% lower risk of colorectal cancer than non-statin users, after adjustment for other known risk factors 97 . In another study, statins decreased patient mortality across various cancer types, regardless of whether they were taken before or after cancer diagnosis [98][99][100][101] . Experiments on leiomyoma have shown that simvastatin treatment not only inhibits cell proliferation and enhances cell apoptosis, but also suppresses levels of extracellular matrix proteins 102 .…”
Section: Targeting Cholesterol Metabolism For Cancer Therapymentioning
confidence: 96%
“…116,117 Recently, a large study of more than 4000 veterans with multiple myeloma demonstrated a 12-month overall survival advantage in individuals with multiple myeloma on a statin. 118 Similarly, in a large study by Nielsen and colleagues 119 of the Danish population with a cancer diagnosis between 1995 and 2007, there was a reduced cancer mortality among statin users compared with those who had never used statins in 13 different types of cancers (adjusted HR for death of any cause 0.82; 95% CI, 0.81–0.85).…”
Section: Cardiac Risk Factors and Cancer Outcomesmentioning
confidence: 97%